ANALISIS KADAR ASAM URAT WANITA DEWASA USIA 40-60 TAHUN SETELAH KONSUMSI JUS TOMAT-JERUK NIPIS - Iffania Karimatur Rasyada; Mohammad Jaelani; Wiwik Wijaningsih (Poltekkes Kemenkes Semarang, 2017)
Background : The prevalence of gout arthritis in Indonesia there is no definitive data. Epidemiological surveys conducted in Bandungan, Central Java on WHO-COPCORD cooperation on 4,683 samples aged between 15-65 years found that the prevalence of gout arthritis in women was 11.7% (Darmawan, 2003). The use of drugs aimed at lowering uric acid levels can cause some side effects, such as nausea, vomiting, and diarrhea so that the level of adherence will decrease (M. Adib, 2011). Objective : To analalysis determine the effect of tomato-lemon juice on uric acid level of adult women aged 40-60 years. Methods : A true experimental research design type with a randomized pretest-posttest control group design. Number of respondents 20 treatments and 18 controls. Intervention was performed for 21 days with the measurement of uric acid at before and after intervention. The test used is paired t test, independent t test and ANCOVA with 95% confidence degree. Result : paired t test showed no difference of pre and post in treatment group (p0,05). Analysis of the effect on the group with normal uric acid category p = 0.655, in the pre hyperuricemia group p = 0.235 and in hyperuricemia p = 0.221. There was a decrease in uric acid levels by 0.26 mg / dl in hyperuricemia but not significant. ANCOVA results show that juice will give significant effect if controlled with initial uric acid level (p = 0,00). Conclusion : There was no effect of tomato-lime juice consumption on uric acid levels, but there was a decrease of 0.26 in the hyperuricemia group but not significant. It is recommended to do further research on hyperuricemia.